A comprehensive closed form micromechanics model for estimating the elastic modulus of nanotube-reinforced composites - Anumandla, V.; Gibson, R.F.
This paper describes an approximate, yet comprehensive, closed form micromechanics model for estimating the effective elastic modulus of carbon nanotube-reinforced composites. The model incorporates the typically observed nanotube curvature, the nanotube length, nd both 1D and 3D random arrangement of the nanotubes. The analytical results obtained from the closed form micromechanics model for nanoscale representative volume elements and results from an equivalent finite element model for effective reinforcing modulus of the nanotube reveal that the reinforcing modulus is strongly dependent on the waviness, wherein, even a slight change in the nanotube curvature can induce a prominent change in the effective reinforcement provided. The micromechanics model is also seen to produce reasonable agreement with experimental data for the effective tensile modulus of composites reinforced with multi-walled nanotubes (MWNTs)and having different MWNT volume fractions.
Keywords: A. NANO-STRUCTURES; B. ELASTICITY; C. ANALYTICAL MODELING, MICRO-MECHANICS